IKLAN ROKOK BIJAK BERNUANSA POLITIK JANGAN MAU DIADU - Joko Suryono; Bono Setyo; Purwani Indri Astuti; Nuryani Tri Rahayu (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
This paper will examine the phenomenon of the construction of the meaning of La Light Wise Cigarette Ads Politically nuanced Do not Want Pitted, using semiotic analysis. The purpose of this paper is to obtain the construction of verbal and non-verbal messages of L.A Wise Cigarette Ads. Politically nuanced Don't Want to Be Pitted. Data in the form of image segments amounted to 8 verbal and non verbal messages. The results showed that La Light Wise Cigarette Ads with Political Shades Don't Want to Be Pitted aims to educate the public, to think critically and wisely, to make bold decisions individually or in groups, out of tension, fierce battles, insulting each other, taunting each other, hitting each other in the 2019 presidential election in Indonesia, which threatens unity and integrity. We do not want to be pitted by parties who have an interest in using the presidential election situation, in order to divide unity and integrity. We are still brothers and sisters as one nation, the nation of Indonesia.